(untitled) (Research, Society and Development, 2021)
Over the years, the useful life of buildings can suffer a natural degradation or influencing human actions. These degradations, in a way, can affect the safety, aesthetics, use and durability of buildings. Pathological manifestations bring inconvenience not only to the client, but also to the builder, as the costs of an eventual intervention after the delivery of the work are greater when compared to the costs of a well-done execution. Therefore, it is interesting to know the phases of the design process of a building, in order to know its construction history and the origin of the problem, and then point out in which phase of the process the error occurred and how this pathology can be resolved. This article portrays a case study in a building located in the city of São Luís – MA. In this study, a survey of the pathologies found in the residence was carried out in order to identify the possible causes and possible solutions for the problems found. In the process, an inspection was carried out at the study site, where it was possible to verify the large presence of moisture in the masonry of the property, which, after a long period of exposure of the walls to the effects of moisture, ended up becoming a predominant factor for the emergence of these pathological manifestations.